ANALISIS PENERAPAN PSAK 71 TERHADAP PEMBENTUKAN CADANGAN KERUGIAN PENURUNAN NILAI DAN KINERJA KEUANGAN PADA ENTITAS PERBANKAN YANG TERHADAFTAR DI BEI (PERIODE 2020-2024) - Purba, Sasmalita Laurensia; Sagala, Indah Cahya; Pane, Aditya Amanda (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
According to the Financial Accounting Standards Statement from PSAK 55 to PSAK 71, banks must use the Expected Credit Loss (ECL) method to calculate the Impairment Loss Reserve (CKPN). Bank ECL uses a forward-looking approach to assess macroeconomic conditions, which sets the CKPN from the beginning of the loan. Unlike the initial implementation of PSAK 71, the COVID-19 pandemic was relatively mild. This research aims to analyze the impact of implementing PSAK 71 on the formation of CKPN and financial performance. Financial performance is measured thru the BOPO, CAR, NPL, and ROA ratios. The sample used in this study consists of 10 (ten) banks listed on the Indonesia Stock Exchange for the period 2020- 2024. Sampling was conducted using a non-probability sampling method. The research type is descriptive-analytic quantitative with the data being financial statements. The research results indicate that the implementation of PSAK 71 and the COVID-19 pandemic impacted financial statements in 2020 and 2021, namely an average increase in CKPN of 132.71% and 137.78%, as well as varied changes in financial performance. However, on average, there were changes in BOPO of 260.64% and 235.74%, CAR of 77.85% and 77.48%, NPL of 100.53% and 87.43%,